2021
DOI: 10.3390/ijerph18010329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Workplace Bullying and Risk Groups in Chinese Employees in Hong Kong

Abstract: Most studies on workplace bullying have been conducted in high-income countries and on Caucasian samples. Little is known about workplace bullying in Asian countries despite its recognition as a serious public health issue in the workplace. We examined the annual and lifetime prevalence of workplace bullying and its risk factors among Chinese employees in Hong Kong. The study was part of a larger project consisting of two waves. Respondents were recruited from a convenience sampling technique and completed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
3
4
0
Order By: Relevance
“…The findings support a wide range of prevalence percentages reports from previous studies affirming that workplace bullying is widespread worldwide (Leon-Perez et al, 2021;Ng & Chan, 2021;Reknes et al, 2019;Jacobson et al, 2014;Giorgi, 2012), reported 14% of the world workforce since a decade ago (Nielsen et al, 2010). In addition, a recent study among 2657 workers in Hong Kong revealed that the phenomenon's annual and lifetime prevalence rate was 39.1% and 58.9%, respectively (Ng & Chan, 2021). Another recent study among 47 Malaysian companies comprising 5,235 participants reported that 39.1% were victims of workplace bullying (Chan et al, 2019).…”
Section: The Prevalence Of Workplace Bullying In Mnc Hrsscsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings support a wide range of prevalence percentages reports from previous studies affirming that workplace bullying is widespread worldwide (Leon-Perez et al, 2021;Ng & Chan, 2021;Reknes et al, 2019;Jacobson et al, 2014;Giorgi, 2012), reported 14% of the world workforce since a decade ago (Nielsen et al, 2010). In addition, a recent study among 2657 workers in Hong Kong revealed that the phenomenon's annual and lifetime prevalence rate was 39.1% and 58.9%, respectively (Ng & Chan, 2021). Another recent study among 47 Malaysian companies comprising 5,235 participants reported that 39.1% were victims of workplace bullying (Chan et al, 2019).…”
Section: The Prevalence Of Workplace Bullying In Mnc Hrsscsupporting
confidence: 90%
“…Therefore, most of the employees experience work-related bullying in the pursuit of contributing to the organizational goal while influencing the prevalence rate of the phenomenon in MNC HRSSC. The findings support a wide range of prevalence percentages reports from previous studies affirming that workplace bullying is widespread worldwide (Leon-Perez et al, 2021;Ng & Chan, 2021;Reknes et al, 2019;Jacobson et al, 2014;Giorgi, 2012), reported 14% of the world workforce since a decade ago (Nielsen et al, 2010). In addition, a recent study among 2657 workers in Hong Kong revealed that the phenomenon's annual and lifetime prevalence rate was 39.1% and 58.9%, respectively (Ng & Chan, 2021).…”
Section: The Prevalence Of Workplace Bullying In Mnc Hrsscsupporting
confidence: 86%
“…Substantial numbers of people who are failing to flourish and may be classified as “languishing” (Keyes, 2006 ; Keyes and Westerhof, 2012 ; Nelson and Padilla-Walker, 2013 ). About 20–25 percent of people struggle with mental health problems (Baumeister and Härter, 2007 ), 25 percent of youth experience a traumatic event (Perkonigg et al, 2000 ), and 50 percent of people experience some form of workplace bullying (Chatziioannidis et al, 2018 ; Ng and Chan, 2021 ). Many people who are languishing fail to receive help (Ciarrochi et al, 2002 ; Cusack et al, 2006 ; Sheppard et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are easily bullied owing to the nature of their tiring and highly intensive work (Karatuna et al, 2020). Epidemiological studies from different countries have shown that up to 39.1%–65.8% of nurses have suffered from workplace bullying (Ng & Chan, 2021; Serafin & Czarkowska‐Pączek, 2019). Workplace bullying has been related to a reduction in job satisfaction (Trépanier et al, 2015) and engagement (Rasool et al, 2021), as well as increased levels of sickness, absenteeism (Kivimäki et al, 2000) and turnover (Park & Choi, 2019).…”
Section: Introductionmentioning
confidence: 99%